Combined Method for tragectory syntheses of assambly and welding robotic-manipulators in workspace with obstacles - M. M. Kozhevnikov; O. A. Chumakov; I. E. Ilushin; A. V. Starovoitov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
A new method is proposed for trajectory syntheses of assembly and welding robotic manipulators in workspace with obstacles, which in contrast to known effectively take in to account complex shape of the elements of the robotic technological cell. The effectiveness of the proposed method is confirmed by the tests results.